2018
DOI: 10.1177/0748233718788989
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic alterations induced by flupyradifurone, a new butenolide insecticide, in human lymphocytes

Abstract: Flupyradifurone (FPD), a member of the new class of butenolide insecticides, acts on nicotinic acetylcholine receptors. Studies on genotoxic and carcinogenic effects of FPD are very limited. This is the first study to investigate the cytotoxic and genotoxic effects of FPD and its metabolites on human lymphocyte cultures with or without a metabolic activation system (S9 mix) using chromosomal aberration (CA) and micronucleus (MN) tests. The cultures were treated with 85, 170, and 340 µg/ml of FPD in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…For the toxicological endpoint category genotoxicity, the PPR Panel concluded, following detailed assessment of the available evidence and uncertainties, that moving to the EKE was not necessary. The available evidence from the study by Sekeroglu et al ( 2018 ) is not able to modify the conclusion reached by EFSA ( 2015a ). The details of the uncertainty analysis showed that in this in vitro study there was a statistically significant increase in chromosomal aberrations without metabolic activation at the two highest concentrations tested and that the number of micronuclei was statistically significant increased at all the concentrations tested with metabolic activation and at the highest concentration tested without metabolic activation.…”
Section: Human Healthmentioning
confidence: 80%
See 2 more Smart Citations
“…For the toxicological endpoint category genotoxicity, the PPR Panel concluded, following detailed assessment of the available evidence and uncertainties, that moving to the EKE was not necessary. The available evidence from the study by Sekeroglu et al ( 2018 ) is not able to modify the conclusion reached by EFSA ( 2015a ). The details of the uncertainty analysis showed that in this in vitro study there was a statistically significant increase in chromosomal aberrations without metabolic activation at the two highest concentrations tested and that the number of micronuclei was statistically significant increased at all the concentrations tested with metabolic activation and at the highest concentration tested without metabolic activation.…”
Section: Human Healthmentioning
confidence: 80%
“…After a screening, only one of the two references (RefID 10 – Sekeroglu et al, 2018 ) was considered further in the assessment. The reference contained information on in vitro lines of evidence for the genotoxicity assessment endpoint category.…”
Section: Human Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…macrophages, lymphocytes, etc. ), leading to the onset of a pro-inflammatory microenvironment responsible for the accumulation of genetic damages and, in turn, for the accumulation of altered cells that were not correctly removed by the immune system [22,23]. Indeed, it is well known that macrophages alterations, and in particular the abnormal secretion of several secreted proteins, play a key role in tumorigenesis and autoimmune diseases [[24], [25], [26], [27], [28]].…”
Section: Introductionmentioning
confidence: 99%